Regenerative surgery of the complications with Morton's neuroma surgery: use of platelet rich plasma and hyaluronic acid. Issue 4 (14th June 2012) - De Angelis, Barbara; Lucarini, Lucilla; Orlandi, Fabrizio; Agovino, Annarita; Migner, Alessia; Cervelli, Valerio; Izzo, Valentina; Curcio, Cristiano
<x xml:space="preserve">Abstract</x> Morton's neuroma is an entrapment neuropathy of the plantar digital nerve. We treated five patients with wound dehiscence and tendon exposure, after Morton's neuroma surgery excision using a dorsal approach. In this article we describe our technique. From July 2010 to August 2011, at the Department of Plastic and Reconstructive Surgery, University of Rome 'Tor Vergata', five patients (four females and one male), with ages ranging between 35 and 52 years, were treated with a combination of PRP (platelet rich plasma) and HA (hyaluronic acid). Thirty days following surgery, all patients showed a complete healing of the wound. The use of this technique for the treatment of postoperative wound dehiscence and tendon exposure has proven as satisfactory.